Effects of Circumpapillary Retinal Nerve Fiber Layer Segmentation Error Correction on Glaucoma Diagnosis in Myopic Eyes - Yanin Suwan (2018)
© Copyright 2018 Wolters Kluwer Health, Inc. All rights reserved. Purpose: In a myopic population, we investigated the occurrence of circumpapillary retinal nerve fiber layer (RNFL) segmentation errors that required manual correction in optical coherence tomography (OCT) and its effect on glaucoma diagnostic capability of OCT. Materials and Methods: Myopic subjects (spherical equivalent refractive error <-3 D) with and without primary open-angle glaucoma were recruited. Three circumpapillary RNFL scans with diameters of 3.45, 4.50, and 6.00 mm were obtained using spectral-domain OCT. RNFL segmentation errors were manually corrected. Receiver operating characteristic curves of retinal nerve fiber layer thickness (RNFLT) were obtained and area under the curves were calculated before and after manual correction. Results: In total, 90 myopic eyes with glaucoma (90 patients; visual field mean deviation, -9.5±7.1 dB) and 58 myopic eyes without glaucoma (58 control subjects) were included. Glaucomatous eyes required manual correction more frequently than control eyes (56% vs. 32% of RNFL OCT scans; P<0.001). After manual correction in the glaucoma group, the global RNFLT decreased significantly from 61.8 to 57.5 μm (P=0.025), 50.8 to 47.2 μm (P=0.019), and 45.5 to 39.6 μm (P=0.006) for the 3.45-, 4.50-, and 6.00-mm scans, respectively. After manual correction of RNFL segmentation errors, the glaucoma diagnostic capability of the global RNFLT improved significantly; the area under the curves increased from 0.827 to 0.886 (P=0.017), 0.829 to 0.880 (P=0.033), and 0.762 to 0.846 (P=0.006) for the 3.45-, 4.50-, and 6.00-mm scans, respectively. Conclusions: A significant proportion of myopic eyes had RNFL segmentation errors in automated spectral-domain OCT analysis, decreasing glaucoma diagnostic capability of OCT RNFLT measurement.